Analisis Pengendalian Internal Sistem Informasi Akuntansi Di Kantor Pos Pringsewu - Amalia, Issabella Sofie; Sawitri, Riska Agi (Labkat Press KA FTIK UNIKOM, 2023)
Information technology is currently experiencing a very rapid development, companies in operating their business already use a computerized system to access all activities carried out by the company. An information system is a system that collects, controls, and manages data to extract information needed by users for specific purposes. A good accounting information system and internal control will help the company to achieve its goals. The purpose of this study was to analyze the internal controls on the N2 and SOPP Pospay systems applied at the Pringsewu branch post office, Lampung, Indonesia and discuss how internal controls on the use of accounting information systems at PT Pos Indonesia Pringsewu branch. This research uses a qualitative descriptive method. The theory used in this research is the Technology Acceptance Model (TAM) theory. The method used is descriptive qualitative with a case study approach because researchers want to explore information that can finally be drawn conclusions from a case. Data collection methods in this study are interviews, observation, and documentation. The results showed that the use of the N2 System and SOPP Pospay at the Pringsewu post office has not gone well in helping manage transactions. There are risks in using N2 and Pospay in recording the wrong amount of revenue, the document number is still manual so that there is fraud in recording it, the software often errors. Internal control that must be carried out by PT Pos KC Pringsewu is system improvement, separation of responsibilities for authorizing transaction recording.